2020
DOI: 10.1021/acs.energyfuels.9b03501
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Nanofluids and Their Applications in Enhanced Oil Recovery: A Comprehensive Review

Abstract: Nanofluids are stable mixtures of nanoscale particles dispersed in base fluids with good prospects in enhanced oil recovery in the petroleum industry. In this review, the mechanisms and evaluation methods of stable nanofluids were analyzed. The effects of nanoparticles on viscosity, electrical conductivity, and surface/interfacial tension of base fluids were discussed. The results of laboratory research and field tests revealed that nanofluids could improve the oil recovery through plugging and profile control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 123 publications
2
49
0
1
Order By: Relevance
“…Therefore, the 0.5 wt% nanoparticle-laden droplets are the most prone to deformation under the electric field. For the1 and 2 wt% nanoparticle-laden droplets, although the interfacial tension is lower than that of pure water droplets, the particles get adsorbed on the surface and form a rigid particle film [ 9 ], which can hinder the deformation of the droplets under electric field force, resulting in a lesser degree of deformation. Moreover, when the particle concentration increases, more particles are adsorbed on the droplet surface, and the particle film becomes more rigid; thus, the droplets are not easily deformed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the 0.5 wt% nanoparticle-laden droplets are the most prone to deformation under the electric field. For the1 and 2 wt% nanoparticle-laden droplets, although the interfacial tension is lower than that of pure water droplets, the particles get adsorbed on the surface and form a rigid particle film [ 9 ], which can hinder the deformation of the droplets under electric field force, resulting in a lesser degree of deformation. Moreover, when the particle concentration increases, more particles are adsorbed on the droplet surface, and the particle film becomes more rigid; thus, the droplets are not easily deformed.…”
Section: Resultsmentioning
confidence: 99%
“…Injected SiO 2 nano-fluids can be re-extracted from the ground along with oil to form oil–water mixtures containing NPs during crude oil extraction. The shear forces of transporting such mixtures in pipelines significantly promotes the formation of oil–water emulsions, and the presence of other substances such as fine particles and salts may further improve the stability of emulsions [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar approaches have been implemented in 12 wells of Shengli and Zhongyuan oilfields, where surface-modified SiO 2 nanoparticles where able to reduce the pressure drop and increase the water injection. For instance, in well #14–#71, the water injection pressure was reduced from 17 MPa to 3 MPa.…”
Section: Applications For Secondary Recovery and Enhanced Oil Recover...mentioning
confidence: 99%
“…Mbbl with high cost-effectiveness Zabala et al 22 ongoing expansion expansion in Colombian oilfields Algyo field, Hungary silica nanoparticles at 1000 mg/L in a silicate/polymer gel system reduction of ∼45% of the water cut in two years; oil cut increased up to 80% Lakatos et al 28 wettability alteration 2020 Colombia nanocapsules of a shell composed of a nonpolar material with a surfactant core in one well, a decrease in total fluid production in 300 BFPD, positive impact on OPEX with constant crude oil production own source in another well, a decrease of 360 bfpd in total production with constant oil production was observed; 7% increase in the productivity index Shengli and Zhongyuan oilfields also showed a decrease in the injection pressure Chunyuan et al 37 Yakasai et al 38 Sun et al 39 Ke and Wei them is the technical-economic feasibility. For example, it can be seen in different studies that the concentration and dose of nanomaterials can be extremely high, which can cause severe formation damage problems during EOR operations and increase application costs.…”
Section: Introductionmentioning
confidence: 99%
“…Such a high research interest is mainly due to the reported (earlier and current) improved thermophysical properties and heat transfer coefficients compared to base liquids with poor thermal characteristics, and for nanofluids potential in thermal management applications. Besides the mentioned improvements and cooling applications, nanofluids have found so far research-based application areas including solar collectors ( [2] , [3] , [4] , [5] ), photovoltaics [6] , and enhanced oil recovery [7] , to name a few. While research on thermal properties of nanofluids has remained the focus of most of the studies, research on surface tension and wetting behavior of this new generation fluids is very limited.…”
Section: Introductionmentioning
confidence: 99%